Improving Oral Language Skills Through Storytelling in Group B of Dasa Wisma Ketong Kindergarten - Dina Purnamasari; Nurhayati Nurhayati; Armina Muthar; Andi Agusniatih (Universitas Al-Hikmah Indonesia, 2025)
Early childhood education contributes significantly to building the foundation of children's development, including language, which is the foundation of communication, early literacy, and social-emotional skills. However, observations show that most children aged 5–6 years still experience difficulties in oral language, such as difficulty telling stories, difficulty answering questions, and limited vocabulary. The purpose of this study was to improve children's oral language skills through the application of interactive storytelling methods. The study used the Classroom Action Research (CAR) design model of Kemmis & Mc Taggart, which was implemented in two cycles on 10 children in Group B of Kindergarten. Data collection was carried out through observation, performance assessment, interviews, and documentation, then analyzed qualitatively with triangulation of techniques and sources. The results showed an increase in oral language skills in three main aspects, namely fluency, accuracy, and vocabulary. In the first cycle, the majority of children were in the